Transforming Academic Policy Through Lecturer Involvement: A Study at the Program Level - Riznada Mutiashafa; Alil Ulmi; Muhammad Saiful Anwar (Universitas Nurul Jadid, 2025)
This study aims to analyze the form, factors, and impact of lecturers' participation in the formulation of education policies in the Education Policy Study Program, Faculty of Education. Using a qualitative approach with a case study design, data was collected through semi-structured interviews and institutional document analysis. The results of the study show that lecturer participation not only takes place in formal forums such as study program meetings, curriculum teams, and quality assurance forums, but also through informal forums such as open discussions and personal initiatives. This participation has a direct impact on academic policies, including in the revision of the 2025 curriculum, the development of contextual learning methods, and the improvement of the quality of educational services. The study also found that lecturer participation is supported by open leadership, an inclusive academic culture, and career incentives. However, challenges remain, such as high workloads, time constraints, and inequality of academic qualifications. These findings strengthen the argument that lecturer participation is a strategic element in participatory and adaptive higher education governance. This study recommends strengthening internal mechanisms to accommodate lecturers' involvement more substantially and sustainably in the institutional policy-making process.